2022
DOI: 10.12659/aot.937988
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Everolimus-Facilitated Tacrolimus Reduction in Living-Donor Liver Transplant Recipients with Hepatocellular Carcinoma

Abstract: Background The study objective was to evaluate the effect of everolimus (EVR) in combination with reduced tacrolimus (rTAC) compared with a standard TAC (sTAC) regimen on hepatocellular carcinoma (HCC) recurrence in de novo living-donor liver transplantation recipients (LDLTRs) with primary HCC at liver transplantation through 5 years after transplantation. Material/Methods In this multicenter, non-interventional study, LDLTRs with primary HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This is one of the largest single-center series on the use of EVR in recipients of a liver graft for HCC, with long-term follow-up data available in the international literature. Despite the expansion of the practice of LT for advanced HCC, information on the impact of EVR or SRL is derived mainly from systematic reviews and meta-analyses incorporating both drugs [11,[36][37][38][39][40], with only a few multi-institutional research studies [9,[41][42][43] and real-life clinical series [44][45][46]. Although some authors dispute the advantage of mTORi for the reduction of post-transplant HCC recurrence [43], the overall evidence originating from these studies supports the use of mTORi for patients with HCC, earlier drug introduction and higher exposure levels to achieve more significant antiproliferative activity [46].…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the largest single-center series on the use of EVR in recipients of a liver graft for HCC, with long-term follow-up data available in the international literature. Despite the expansion of the practice of LT for advanced HCC, information on the impact of EVR or SRL is derived mainly from systematic reviews and meta-analyses incorporating both drugs [11,[36][37][38][39][40], with only a few multi-institutional research studies [9,[41][42][43] and real-life clinical series [44][45][46]. Although some authors dispute the advantage of mTORi for the reduction of post-transplant HCC recurrence [43], the overall evidence originating from these studies supports the use of mTORi for patients with HCC, earlier drug introduction and higher exposure levels to achieve more significant antiproliferative activity [46].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is one of the largest single-center series on the use of EVR in recipients of a liver graft for HCC, and with long-term follow-up data available in the international literature. Despite the expansion of the practice of LT for advanced HCC, information on the impact of EVR or SRL is derived mainly from systematic reviews and meta-analyses incorporating both drugs (11,(36)(37)(38)(39)(40), with only a few multi-institutional research studies (9,(41)(42)(43) and real-life clinical series (44)(45)(46). Although some authors dispute the advantage of mTORi for the reduction of posttransplant HCC recurrence (43), the overall evidence originating from these studies supports the use of mTORi for patients with HCC, suggesting earlier drug introduction and higher exposure levels to achieve greater antiproliferative activity (46).…”
Section: Discussionmentioning
confidence: 99%
“…According to a retrospective analysis by Sapisochin et al, an early start of everolimus administration is advised. The authors found that early initiation of an everolimus-facilitated tacrolimus (TAC) reduction lowers the rate of HCC recurrence compared to tacrolimus control (3.6% vs. 11.5%, p = 0.136) at 5 years after LT [ 30 ]. Moreover, analysis of patients who received an everolimus-based immunosuppressive regimen showed a correlation between drug blood concentration and recurrence rate, with lower HCC recurrence rates in patients with mean trough levels of everolimus >6 ng/mL [ 67 ].…”
Section: Mtori and Hcc Recurrencementioning
confidence: 99%
“…When mTORi are used in LT recipients, no difference can be found in acute graft rejection rate compared to a CNI-based regimen (RR 1.1, 95%, CI 0.94–1.28) [ 65 ]. This non-inferiority in preventing graft rejection has been proven for both sirolimus and everolimus and can be ascribed to mTORi suppressive action on the immune system [ 20 , 30 , 92 , 95 ]. Mainly, rapamycin and its derivatives promote the expansion of Treg at the expense of other CD4+ subgroups by altering APCs activity and T cells polarization, thus favoring immunological tolerance against the graft [ 13 , 59 , 96 ].…”
Section: Mtori In Immunosuppression After Ltmentioning
confidence: 99%